1998
DOI: 10.3109/00048679809062728
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Psychiatric Illness and the Circadian Pattern of Heart Rate

Abstract: The presented findings together suggest that there is a systematic relationship between psychiatric status and heart rate in which core physiological differences between certain states are reflected in distinctively different circadian patterns of activity. The state-dependent nature of this relationship suggests obvious practical applications, and examples are given of how these adjunct data can provide objective indices of clinical status and change. At a theoretical level, the physiological dimension reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 16 publications
1
36
0
2
Order By: Relevance
“…Although the mechanisms of this risk are unclear, depression is associated with other risk factors for cardiac events including elevated heart rate (HR) and low heart rate variability (HRV) (Carney et al, 2005b; Kemp et al, 2010), dysfunctional sleep (Buysse et al, 1998; Ford et al, 1989), and blunted circadian HR rhythm (Stampfer, 1998; Taillard et al, 1990). Following an acute myocardial infarction (MI), for example, compared to non-depressed patients those with depression have higher nighttime HRs (Carney et al, 2008), lower heart rate variability (Carney et al, 2001), and a greater likelihood of having little or no decrease in nighttime HR relative to daytime levels (nocturnal dip) (Carney et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms of this risk are unclear, depression is associated with other risk factors for cardiac events including elevated heart rate (HR) and low heart rate variability (HRV) (Carney et al, 2005b; Kemp et al, 2010), dysfunctional sleep (Buysse et al, 1998; Ford et al, 1989), and blunted circadian HR rhythm (Stampfer, 1998; Taillard et al, 1990). Following an acute myocardial infarction (MI), for example, compared to non-depressed patients those with depression have higher nighttime HRs (Carney et al, 2008), lower heart rate variability (Carney et al, 2001), and a greater likelihood of having little or no decrease in nighttime HR relative to daytime levels (nocturnal dip) (Carney et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, impaired sleep and daytime fatigue are included in the diagnostic criteria for depressive disorders (American Psychiatric Association, APA, 2000) where diurnal variations in symptoms (e.g., mood and psychomotor activity) have frequently been reported. These fluctuations are reflected in physiological measures such that, compared to a control population, depressive patients show alterations in circadian rhythms of melatonin and (Pacchierotti et al, 2001) cortisol levels (Deuschle et al, 1997); body temperature (Daimon et al, 1992); and heart rate (Stampfer, 1998). Moreover, some interventions that change the timing of the biological clock in the brain (e.g., sleep deprivation, light therapy) have efficacy as treatments for these conditions (Wehr et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…(29) There is evidence that not only do depressed but otherwise medically well psychiatric patients have higher 24-hour HR than nondepressed comparison groups, but the difference in HR between depressed and nondepressed patients is more pronounced at night than during the day. (30-32) Sleep disturbance is a common symptom of depression(33, 34), and it may help to explain the higher nighttime HR in depressed patients. (30) Polysomnographic studies have found differences in sleep architecture, as well as more frequent arousals and poorer sleep efficiency, in depressed psychiatric patients compared to controls.…”
Section: Introductionmentioning
confidence: 99%